2002
DOI: 10.1097/00000539-200203000-00021
|View full text |Cite
|
Sign up to set email alerts
|

The Neuromuscular Transmission Module Versus the Relaxometer Mechanomyograph for Neuromuscular Block Monitoring

Abstract: Compared with the Relaxometer mechanomyograph, the neuromuscular transmission module could equally indicate time to tracheal intubation and full recovery from 0.6 mg/kg rocuronium neuromuscular block. Its small quick-fit sensor has the advantage, in an often crowded and busy operating room, of being incorporated in the AS/3(TM) anesthesia workstation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 9 publications
0
27
0
1
Order By: Relevance
“…7 Two EKG electrodes were placed on the patient's wrist at the ulnar nerve, and the evoked muscle response at the adductor pollicis (AP) muscle was measured by the displacement of the probe positioned between the patient's thumb and forefinger. After automatic calibration, supramaximal TOF stimulation ([ 50 mA) was applied every 15 sec, and TOF ratio (TOFR) values were displayed on the monitor screen.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…7 Two EKG electrodes were placed on the patient's wrist at the ulnar nerve, and the evoked muscle response at the adductor pollicis (AP) muscle was measured by the displacement of the probe positioned between the patient's thumb and forefinger. After automatic calibration, supramaximal TOF stimulation ([ 50 mA) was applied every 15 sec, and TOF ratio (TOFR) values were displayed on the monitor screen.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Dahaba et al 3 compared KMG and MMG for monitoring NMB in 20 patients after rocuronium 0.6 mg·kg -1 . They found that although both methods showed good agreement to determine recovery to TOF-ratio of 0.8, KMG lagged behind in determining the full course of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…They found that although both methods showed good agreement to determine recovery to TOF-ratio of 0.8, KMG lagged behind in determining the full course of recovery. However, Dahaba et al 3 did not determine the course of recovery by using different TOF-ratios, but recovery to different levels of first twitch heights. This might highlight differences between the two methods more than when recovery is determined by using different TOF-ratios as done in the current study -and in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations